Analisis Perancangan dan Implementasi Sistem Penjualan Kredit Berbasis Web (Studi Kasus : PT RUKUN SEJAHTERA TEKNIK) - Idawati; Muhamad Zen; Nur Khikmah (Institut Sains dan Teknologi Al-Kamal, 2022)
Abstrak Perancangan sistem penjualan kredit berbasis web pada PT. Rukun Sejahtera Teknik perlu dilakukan guna membantu proses kegiatan penjualan yang lebih efektif dan efisien. Kredit yang dimaksud disini adalah sistem pembayaran dengan metode jangka waktu yaitu tempo 30 hari dan tempo 60 hari setelah pelanggan mendapatkan barang yang dibeli. Aplikasi sistem penjualan kredit berbasis web menggunakan metode pengembangan waterfall dengan beberapa tahapan yaitu analisa kebutuhan, desain sistem, penulisan kode program, pengujian program, dan pemeliharaan program. Aplikasi ini dirancang menggunakan UML (unified Modelling Languange), yaitu Use Case Diagram, Activity Diagram, Sequence Diagram dan Class Diagram, MySQL. E-commerce ini dibuat menggunakan bahasa PHP (Personal Home Page) dan Framework Laravel. Kata kunci : Sistem Informasi, Penjualan kredit, Berbasis Web, database, waterfall. Abstract Designing a web-based credit sales system at PT. Rukun Sejahtera Technique needs to be done in order to help the sales process process more effectively and efficiently. The credit referred to here is a payment system with a maturity method of 30 days and 60 days after the customer gets the purchased item. The web-based credit sales system application uses the waterfall development method with several stages, namely needs analysis, system design, writing program code, program testing, and program maintenance. This application is designed using UML (Unified Modeling Language), namely Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams, MySQL. E-commerce is created using the PHP language (Personal Home Page) and the Laravel Framework. Credit sales system design is based on web at PT. Rukun Sejahtera Technique needs to be done in order to help the sales process process more effectively and efficiently. The credit referred to here is a payment system with a maturity method of 30 days and 60 days after the customer gets the purchased item. The web-based credit sales system application uses the waterfall development method with several stages, namely needs analysis, system design, writing program code, program testing, and program maintenance. This application is designed using UML (Unified Modeling Language), namely Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams,MySQL,. E-commerce is made using the PHP language (Personal Home Page) and the Laravel Framework. Keywords: Information Systems, Credit Sales, Web Based, Database, Waterfall.